Embedded Systems Design Flows: Integrating Requirements Authoring and Design Tools - Wolvers, Ronald; Seceleanu, Tiberiu (EUROMICRO (IEEE Computer Society Press), 2013)
In the modern practical reality there are many different tools being used in the various phases of the system development lifecycle. Every tool employs its own underlying metamodel and these metamodels tend to vary greatly in size and complexity, making them difficult to integrate. One solution to overcome this problem is to build a tool integration framework that is based on a single, shared metamodel. We introduce here an OSLC based approach to integration. To validate the framework, an industrial case has been carried out, using several embedded systems tools. To expose tools internal data through Web services, a tool adaptor is needed. This work reports on the development of such an adaptor for the Requirements Management module of HP ALM, as used in the industrial case.